Enemy at the gates : the battle for Stalingrad - Craig, William, 1929- (New York : Reader's Digest Press, 1973)
An account of the stalingrad Epic-Here is the Drama, The Terror, The Horror and the Heroism of the Greatest Military encounter of our time.
Includes bibliographical references (pages 409-420).
Keywords: q -- 1915-1993 or 1994.; q -- 1915-1993 or 1994.; 1942-1943; Stalingrad, Battle of, Volgograd, Russia, 1942-1943.; Bataille de Stalingrad, Volgograd, Russie, 1942-1943.; Schlacht um Stalingrad; Russia (Federation) -- Volgograd; Festschriften; Festschriften